The Factors affecting the implementation of electronic training in health care organization in Saudi Arabia: The case of King Abdulaziz university hospital - Alsomali, Sabah Abdullah; Alghamdi, Amira AbdulAziz (Journal of Economic, Administrative and Legal Sciences, 2019)
The current study focused on the definition of electronic training and the importance of electronic training in the health organizations. The study main objective was to study the most significant factors that are affecting the electronic training application in the health organizations. The researcher used both a descriptive and analytical methods in her study. A questionnaire was used as a tool for data collection; the questionnaire was divided into two sections. The first section contained questions about general information that included: sex – age- qualification – experience in years – computer skills. The second section dealt with questions related to the study hypothesis. This section consists of four parts as follows: The first part included 11 statements about the reality of the electronic training in the health organizations in the present, which is considered the dependent variable in this study. The second part consists of 15 statements; the third part consists of 13 statements. The fourth part consists of 8 statements. These parts addressed the most significant factors that affected the implementation of the electronic training in the health organizations. These were the independent variables of the study. The questionnaire was distributed to a study sample of (368) employee in the hospital. A (200) questionnaire were collected on a rate of 54%. The Results of the study showed that the infrastructure for the Information technology and the government’s tends towards the digital society were the most important factors that primarily affect the possibility of applying the electronic training in the health organizations. The main recommendations of the study were: the need for a support from the high and senior management in the king Abdul Aziz University hospital to adopt the electronic application of the electronic training and manage the resistance of change that many organization faces. The necessity of the electronic training for all the staff on computers skills. Finally, the importance of having a unit for the technical support king Abdul Aziz University hospital.